Statistical reanalysis of vascular event outcomes in primary and secondary vascular prevention trials - Woodhouse, Lisa Jane (2022)
Randomised controlled trials in vascular prevention typically use binary events as the primary outcome. However, this practice is statistically inefficient and gives no indication of the severity of the event. Hypothetically, outcomes could be polychotomised, with ordering determined by severity.